Fostering Rayo’s Product Uniqueness through Batik Training with Sanggar Salingka Tabek - Verni Juita; Fitriyeni Oktaviani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2025)
Sanggar Rangkiang Salayo, a women's business group specializing in knitting, strives for continuous innovation to ensure consumers' sustainability of its product acceptance. One innovative approach involves integrating knitting with batik patterns in each new product. To maintain the sustainability of creating combination products with unique batik motifs that can serve as the hallmark of Rayo products, the Sanggar Rangkiang participated in a training program in collaboration with Salingka Tabek Batik, renowned as a producer of distinctive Solok batik. The training method employed included training and mentoring in both hand-drawn and stamped batik, covering various stages such as fabric washing, design sketching, wax application, and coloring. At each stage, participants received guidance from instructors at the Salingka Tabek batik center. Through this training, members of the Rangkiang Salayo Studio expanded their skills from knitting to mastering hand-drawn and stamped batik and successfully created several batik designs. These designs were later incorporated into woven bag products, adding a unique signature touch and increasing the value of Rayo products in the market.